Sistem Manajemen Pembelajaran Pada SMP Negeri 30 Palembang Berbasis Web - Haryadi Haryadi; Kurniawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The current learning management system is advancing rapidly because it is supported by ICT in order to increase the effectiveness of the teaching and learning process, even the events we are experiencing today are in the form of the Corona Virus Disease 19 (COVID-19) outbreak. Various efforts have been made by the Ministry of Education and Culture (Kemendikbud) to continue carrying out the teaching and learning process, by providing internet package assistance to students to continue to carry out distance learning by instructing all educators at all levels of education to create fun learning from home, both students and teachers. as well as students. Therefore, the teacher's role is needed in managing learning starting from planning (planning), organizing (organizing), implementation (actuating) and evaluation (evaluating). The purpose of this study is to improve the existing system, where previously it was still manual by designing a web-based learning digitization application. In this study, the system studied was using LMS (Learning Management System) and also explained about the database design, input and output design of the system under study with the data collection process several methods used were interviews, observations and literature studies. The design of the system design uses UML (Unified Modeling Language). The results of the Web-Based Learning Management System program at SMP Negeri 30 Palembang using the PHP programming language. This study states that the learning information system at SMP Negeri 30 Palembang with the application of information technology can make it easier for teachers and students in daily tasks so that processing, storing, reporting on teaching and learning outcomes at the school is easier and faster.